Análisis cinemático con GMOS IFU en galaxias de formación estelar violenta: SDSSJ0839 - Bosch, Guillermo Luis (2018)
This work describes a new method for analysing Integral Field Spectroscopic observations of emission line spectra originated in star forming regions, considering the presence of multiple components in the line profile of different ions. Observations were carried out in queue mode using the GMOS attached to the Gemini North Telescope. To achieve this we built a Python code that analyses every individual spectrum of the data cube. Our code applies an iterative process that starts with a single Gaussian fit to each emission line profile starting from a single estimated average velocity of the galaxy. The output of this first approximation is used as the source for the second stage, where a second component is cloned from the first one and the fitting procedure is repeated with this new set of initial guesses. The new output is analysed to check whether there is an actual improvement in the fit from the previous model, using the Akaike Information Criterion indicator. For our GMOS spectra on SDSSJ0839, the largest meaningful number of components was found to be three for the brightest spaxels on the H line profile. The possibility of fitting multiple components to the H line profiles of the data cube allows to perform a much more detailed analysis of the gas kinematics, as the behaviour differs dramatically from what can be inferred from fitting a single Gaussian profile. We were also able to measure fluxes for [Nii], [Sii] among other forbidden lines. With these, we could estimate line ratios linked to temperature and density, even though the wavelength coverage does not allow to obtain values for these physical parameters directly. In this contribution we present the information that this kind of analysis provides on the ionised gas complex kinematics within a starburst galaxy.